Le lapin : de la biologie à l'élevage - Gidenne, Thierry (Savoir faire (Versailles, France), 2015)
This work is the first manual devoted specifically to rabbit biology. It recounts the history of the domestic rabbit and summarises current knowledge. It also makes concrete recommendations on rabbit breeding practices for both families and professionals and for pet rabbits.